2020
DOI: 10.1007/s40256-020-00459-1
|View full text |Cite
|
Sign up to set email alerts
|

Gout Pharmacotherapy in Cardiovascular Diseases: A Review of Utility and Outcomes

Abstract: Hyperuricemia and gout have been linked to an increased risk for cardiovascular (CV) disease, stroke, hypertension, heart failure, and chronic kidney disease, possibly through a proinflammatory milieu. However, not all the drugs used in gout treatment improve CV outcomes; colchicine has shown improved CV outcomes in patients with recent myocardial infarction and stable coronary artery disease independent of lipid-lowering effects. There is resurging interest in colchicine following publication of the COLCOT, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
(59 reference statements)
0
16
0
1
Order By: Relevance
“…A highly intriguing new observation is the potential role of colchicine, an old anti-inflammatory drug used for gout and pericarditis, in COVID-19. Recent RCTs in patients with coronary artery disease have shown significant reduction of CVD events with colchicine treatment [145]. A metaanalysis of eight studies included 5778 COVID-19 patients and 2668 patients who received colchicine treatment [146].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids) Including Colchicinementioning
confidence: 99%
“…A highly intriguing new observation is the potential role of colchicine, an old anti-inflammatory drug used for gout and pericarditis, in COVID-19. Recent RCTs in patients with coronary artery disease have shown significant reduction of CVD events with colchicine treatment [145]. A metaanalysis of eight studies included 5778 COVID-19 patients and 2668 patients who received colchicine treatment [146].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids) Including Colchicinementioning
confidence: 99%
“…In addition, there is a class of clusters focused on rheumatoid arthritis, which is not exploring the comorbid mechanisms of RA and CHD, but instead uses anti-inflammatory drugs to treat rheumatoid arthritis. Recent studies have focused on mechanistic intervention in cardiovascular disease with the anti-inflammatory drugs allopurinol ( 68 , 69 ) and colchicine ( 70 74 ), promising agents for intervention in cardiovascular disease ( 75 ). Moreover, there have been concentrated studies on gastrointestinal toxicity of NSAIDs ( 76 78 ), such as targeting gastrointestinal side effects of anti-inflammatory medications COX-2 inhibitors ( 79 , 80 ), focusing on the drug’s safety, and preventing adverse events ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is a leading cause of mortality in the United States, which stresses the importance of identifying risk factors and working on prevention [18]. Numerous studies have reported gout as an independent risk factor for MI and colchicine significantly lowering the risk of ischemic cardiovascular disease [4,19]. CPPD is a newly emerging risk factor for adverse cardiovascular events, and additional large-scale studies are warranted to explore this relationship further.…”
Section: Discussionmentioning
confidence: 99%